Essential Guide to Dance - Rickett-Young, Linda (London Hodder and Stoughton, 1996)
This text closely follows the A Level dance syllabus, with particular emphasis on the social and cultural context of dance and includes tasks and activities within each chaste
Include Illustration, Indexes
Keywords: Dance -- Dance Steps